Primary cutaneous actinomycosis caused by Actinomyces meyeri as first manifestation of HIV infection - Gomes, J (2012)
Primary cutaneous actinomycosis is very uncommon. We report a patient with cutaneous actinomycosis with multiple lesions without any detectable extra-cutaneous lesions. In our patient the actinomycosis was the presenting manifestation of HIV infection.